Identification of a compound heterozygote in LYST gene: a case report on Chediak-Higashi syndrome - Yinsen Song; Zhengping Dong; Shuying Luo; Junmei Yang; Yuebing Lu; Bo Gao; Tianli Fan (BMC, 2020)
Abstract Background Chediak-Higashi Syndrome (CHS) is a rare autosomal recessive disease caused by loss of function of the lysosomal trafficking regulator protein. The causative gene LYST/CHS1 was cloned and identified in 1996, which showed significant homology to other species such as bovine and mouse. To date, 74 pathogenic or likely pathogenic mutations had been reported. Case presentation Here we describe a compound heterozygote in LYST gene, which was identified in a 4-year-old female patient. The patient showed skin hypopigmentation, sensitivity to light, mild splenomegaly and reduction of platelets in clinical examination. Giant intracytoplasmic inclusions were observed in the bone marrow examination, suggesting the diagnosis of CHS. Amplicon sequencing was performed to detect pathogenic mutation in LYST gene. The result was confirmed by two-generation pedigree analysis base on sanger sequencing. Conclusion A compound heterozygote in LYST gene, consisting of a missense mutation c.5719A > G and an intron mutation c.4863-4G > A, was identified from the patient by using amplicon sequencing. The missense mutation is reported for the first time. Two-generation pedigree analysis showed these two mutations were inherited from the patient's parents, respectively. Our result demonstrated that amplicon sequencing has great potential for accelerating and improving the diagnosis of rare genetic diseases.